High-entropy Ti-Zr-Nb-Hf-Ta carbide and carbonitride coatings fabricated by high-speed arc discharge plasma jet; International Journal of Refractory Metals and Hard Materials; Vol. 135 - Nikitin D. S. Dmitry Sergeevich; Shanenkov I. I. Ivan Igorevich; Nassyrbayev (Nasyrbaev) A. Artur; Sivkov A. A. Aleksandr Anatolyevich; Baydyshev V. S. Viktor Sergeevich; Kvashnina Yu. A. Yulia Aleksandrovna; Matsokin N. A. Nikita Alekseevich; Pak A. Ya. Aleksandr Yakovlevich; Kvashnin A. G. Aleksandr Gennadjevich (2026, 2026)
Title screen